MAIN STRATEGIES OF IMPLEMENTING ALTERNATIVE ASSESSMENT IN ENGLISH LANGUAGE TEACHING (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
In recent years, alternative assessment has become an essential component of effective English language teaching, as it addresses the limitations of traditional testing methods. Unlike standardized exams that focus primarily on discrete language knowledge, alternative assessment emphasizes authentic language use, learner autonomy, and continuous progress. This article explores the main strategies for implementing alternative assessment in English language teaching, including portfolio assessment, project-based assessment, peer and self-assessment, and performance-based tasks. Using a qualitative literature-based approach, the study analyzes how these strategies enhance communicative competence, motivation, and critical thinking skills among learners. The findings suggest that alternative assessment fosters meaningful learning experiences and supports learner-centered pedagogy, although its successful implementation requires clear criteria, teacher training, and institutional support.